Early symptoms of autism spectrum disorders and association with Brazilian children's development and behavior - Rafaela Silva Moreira; Marina Aguiar Pires Guimarães; Lívia de Castro Magalhães; Janaina Matos Moreira; Claudia Regina Lindgren Alves (CoDAS)
ABSTRACT Purpose to examine the association between the early autism spectrum disorder (ASD) signs and developmental and behavioral performance of Brazilian children aged 18 to 34 months. Methods A cross-sectional study with 221 children recruited at public healthcare and early education services. Early symptoms of ASD were screened using the Parental Observations of Social Interaction (POSI). Children's development and behavior were examined using the Ages and Stages Questionnaires (ASQ-3) and Survey of Well-being of Young Children (SWYC-BR). The results of children at risk for ASD were compared to the no-risk ones using Chi-square and t-test. Results The overall frequency of children at risk for ASD (POSI-positive screening) was 33% and did not differ across children's age range and gender. Children at risk for ASD showed worse socio-emotional behaviors (p=0.004) and lower scores for overall development (p=0.0001), communication (p=0.0007), fine motor (p=0.04), and personal-social domains (p=0.01). Differences between groups varied according to children's age and across developmental/behavioral domains and were more evident in older children. Children aged 30 to 34 months presented significant differences in overall development (p=0.001), behavior (p=0.004), and the personal-social domains (p=0.03). Conclusions The frequency of children at risk for ASD was higher than described in the literature. Also, the development and behavior of children at risk for ASD were significantly different from their peers and compatible with the presentation of ASD in young children. Our findings reinforce the need for systematic and holistic surveillance of child development during well-being visits to improve ASD early detection.